Analisis Kompetensi Kepribadian Guru pada SMA Negeri 1 Kampar Timur - Andini Putri; Anggini, Anggini; Dwi Nazwa Adisti; Ade Irma (Politeknik Kampar, 2025)
This study aims to analyze the personality competence of teachers at SMA Negeri 1 East Kampar based on the teacher competency standards in Permendiknas Number 16 of 2007. Personality competence is an important aspect in shaping student character and creating an ethical and inspiring learning environment. The research method used is descriptive qualitative with data collection techniques through interviews and observations of three teachers from different fields of study, namely Indonesian Language, Civics, and Mathematics.The results showed that all teachers interviewed had met the established personality competency standards, with high evaluation scores (range of scores 23-25 out of a total of 25). The teachers showed honesty, responsibility, patience, ability to manage emotions, good professional relationships, and being a role model for students. In addition, they are also able to build trust with students and parents through an empathic and communicative approach.In conclusion, teachers at SMA Negeri 1 Kampar Timur have possessed and applied excellent personality competencies in learning practices, and can be used as role models in strengthening character education at school.